1985
DOI: 10.1017/s0003356100025514
|View full text |Cite
|
Sign up to set email alerts
|

A note on the use of assortative mating in tandem selection

Abstract: Computer simulation was used to study the effect of assortative mating in tandem selection. Selection was applied alternatively for each of two traits of equal economic importance, the mating being assortative for the trait not subjected to selection. Two heritabilities (0-2, 0-4), two selection intensities (20/40, 20/100) and three additive genetic correlations (0-50, 0, -0-50) were considered. Assortative mating gives a response which is 1-03 to 1-10 times that achieved when random mating is employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Assortative mating could be employed in tandem selection, since this method selects only one trait per generation and it is possible to apply assortative mating to the trait not subjected to selection. G arcia and T oro (1985) used computer simulation to show that assortative mating gives a response 1.03–1.10 times stronger than that obtained with random mating. However, tandem selection is much less efficient than index selection, the relative efficiency of index selection being approximately 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…Assortative mating could be employed in tandem selection, since this method selects only one trait per generation and it is possible to apply assortative mating to the trait not subjected to selection. G arcia and T oro (1985) used computer simulation to show that assortative mating gives a response 1.03–1.10 times stronger than that obtained with random mating. However, tandem selection is much less efficient than index selection, the relative efficiency of index selection being approximately 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies (B aker 1973; D e L ange 1974; G arcia and T oro 1985; S mith and H ammond 1987; T allis and L eppard 1987) have shown that the utility of assortative mating to enhance selection response should increase with the character heritability, the phenotypic correlation between mates, and the proportion of selected individuals.…”
Section: Introductionmentioning
confidence: 99%